2021
DOI: 10.1002/app.50409
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformation and dielectric properties of polyvinylidene fluoride/organic‐montmorillonite nanocomposites fabricated under elongational flow field

Abstract: Compounding montmorillonite (MMT) with polymorphic polyvinylidene fluoride (PVDF) by melt intercalation method can induce the crystal phase transformation of PVDF, which is of great significance to obtain the electroactive PVDF. In this research, PVDF/Organic‐Montmorillonite (OMMT) nanocomposites were prepared by a novel vane mixer, which was dominated by the elongational flow field in the whole plasticizing. The dispersion of OMMT, the crystal phase transformation of PVDF, and the resulting properties of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
3
16
0
1
Order By: Relevance
“…A similar mechanism of clay exfoliation induced by the application of the elongational flow has been reported by Tong et al [226] in polyvinylidene fluoride (PVDF)-based nanocomposites containing commercial organo-modified clays obtained in a vane mixer. In particular, as schematically illustrated in Figure 21, in the convergent region, the clay agglomerated are first broken to form stacks of tactoids, which experienced a "double layer peeling" process in the divergent region; moreover, the simultaneous orientation of the PVDF chains facilitates their diffusion within the inter-layer galleries, further inducing the clay exfoliation.…”
Section: Morphology Evolution Of Polymer-based Composites and Nanocomposites Under Elongational Flowsupporting
confidence: 72%
“…A similar mechanism of clay exfoliation induced by the application of the elongational flow has been reported by Tong et al [226] in polyvinylidene fluoride (PVDF)-based nanocomposites containing commercial organo-modified clays obtained in a vane mixer. In particular, as schematically illustrated in Figure 21, in the convergent region, the clay agglomerated are first broken to form stacks of tactoids, which experienced a "double layer peeling" process in the divergent region; moreover, the simultaneous orientation of the PVDF chains facilitates their diffusion within the inter-layer galleries, further inducing the clay exfoliation.…”
Section: Morphology Evolution Of Polymer-based Composites and Nanocomposites Under Elongational Flowsupporting
confidence: 72%
“…(3)矿物辅助单元:不具备直接应用功能属性,但具有辅助功能属性的矿物,如电气石复合材料用于光 催化抗菌应用 [29] , 电气石本身不是光学半导体, 却能自身受激产生载流子用于光催化; 石墨烯不具备发电功能, 但可作为聚偏氟乙烯-六氟丙烯共聚物(PVDF-HFP)薄膜自储能发电的填料调控压电-介电耦合发电 [30] 等。 [32] 、云母 [33] 、蒙脱 石 [34] 、埃洛石 [35] 等为代表的矿物材料表面拥有丰富的官能团或电子云,有利于诱导 PVDF 类高分子形成电活 性的 β 相或者为电荷移动提供路径,且上述材料成本较低,制备工艺简单,是合成复合压电储能器材的理想材 料之一。例如,最新研究表明 [36] ,二维层状云母片内部富含 K + ,在外加电场下可以沿着电场定向移动,使最 初绝缘的云母具有导电性,且通过调节外加电场的大小可进一步在云母器件中得到具有不同单/双开关窗口的 电流-电压特性等阻变特性。又如,以石墨为原料制备的石墨烯是碳基矿物材料的一种,由于其独特的二维结 构、大的比表面积、优异的机械强度、良好的化学亲和性等优点在高分子复合材料领域备受关注,且该材料还 具有一定的电能储存和转化潜力,被证明可以提升 PVDF 基薄膜的压电性能 [37] 。 本研究组 [38] 进行压电-介电耦合。该过程的电压输出强度主要取决于薄膜恢复过程中可用的极化电荷数量和能量增益。这 类石墨烯/高分子压电和介电材料或将促进功能材料系统的发展,且该类复合材料还可应用在传感 [39] 、活性分 子控释 [40] 、表面拉曼增强 [41] 、光催化增强 [42] 等领域(图 2) 。 图 2 (网络版彩色) 基于石墨烯/PVDF-HFP 薄膜的压电感应电荷发生器及其拓展应用 [31] 。 Copyright © 2020, Applications [31] . Copyright © 2020, John Wiley & Sons 2.2 用于超级电容器的矿物复合材料 超级电容器是一种功率密度高和充电速度快的新能源器件 [43,44] ,常常被用作锂离子电池的替代品。其工 作原理分为双电层(EDLC)电容机理和赝电容机理。如果在正负极和电解液之间的两个电荷界面层发生了静 电吸脱附,则称为双电层电容机理;如果发生了高度可逆的氧化还原反应,且没有质量转移局限性,则称为赝 电容机理 [45,46] ;如果能像电池一样能发生快速深入的离子嵌入脱出,则称为插入式赝电容机理。 用于超级电容器的电极材料包括具有双电层电容的碳材料以及具有赝电容的金属氧化物和导电聚合物 [47] 矿 [48] 是由[MnO 6 ]八面体单元沿着 c 轴方向无限共享形成的二维层状薄片。由于具有一定的导电性、合适的层 间距(~0.7 nm) [49,50] 和稳定的层结构,水钠锰矿很容易被 Li + 、Na + 、K + 、H + 、Co 2+ 等阳离子交换、插层、嵌 入或脱出。最新研究表明 [51] ,其电容电荷存储是由层间阳离子插层控制的。同时,由于纳米限域层间结构水的 存在,增加了嵌入阳离子和水钠锰矿主体之间的距离,导致相互作用降低,表现出电容性质,并引起了极小的 结构变化(图 3(a,b)) 。因此,其在锂离子存储和超级电容器方面具有很好的应用前景。为提升水钠锰矿的电 容值并拓展其超级电容器应用,Zhang 等人 [52] 使用碳纤维做还原剂制备了蜂窝状水钠锰矿型 MnO 2 @碳纤维复 合电极材料(图 3(c,d)) ,得到的核壳结构的比电容量在 100 mA g -1 时达到 295.…”
Section: 矿物复合材料是指组成复合材料的多种组分中, 含有一种或多种矿物组分从而使材料具有新性能的多相固unclassified
“…[1][2][3][4][5][6][7][8] Most of the studies have concluded that the nanoclay structures (i.e., the amounts of exfoliated or intercalated and the sizes of tactoids) in the host polymer matrices predominantly rule the useful properties of such hybrid nanocomposites. [1][2][3]6,[8][9][10][11][12][13] So with the consideration of this fact, enormous attempts had been made to achieve better homogeneous dispersion of loaded nanoclay platelets in the PEO matrix by adopting different preparation methods. 5,6,[9][10][11] Furthermore, numerous researches evidenced that the loading of treated-nanoclay in the polymer matrices formed highly successful nanocomposites of improved thermal and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Among the researches on nanoclay dispersed polymer matrix-based various PNCs, the semicrystalline PEO matrix is highly attempted because of its linear chain structure, hydrophilic character, low melting temperature, and good flexibility and biodegradability of the film. 5,6,[9][10][11]13 Besides huge exfoliation, there is always formation of intercalated structure in the PEO/clay nanocomposite, and their amounts are highly influenced by the type of dispersed nanoclay (sodium-montmorillonite (Na + -MMT, commonly denoted by MMT) or organomodified-montmorillonite (OMMT)) in the PEO matrix and also the adopted methods for nanocomposite preparation (solution-cast or melt-compounding). 5,6,[9][10][11] In addition to the alterations in chemical and thermomechanical properties of the PNCs, it is also observed that the dielectric and electrical properties of nanoclay loaded polymer matrices are largely affected by the intercalated/exfoliated clay structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation